Thermal and day-lighting performance of aerogel glazing system in large atrium building under cooling-dominant climates. (February 2019) - Yang, Yanping; Wu, Huijun; Yang, Lixiu; Xu, Tao; Ding, Yunfei; Fu, Ping
Abstract: Achieving low energy consumption and maintaining proper day-lighting environment is a challenge for large atrium building under cooling-dominant climates. Fortunately, aerogel glazing system has recently been considered to have great potential in energy-saving applications for architectural glass due to its special light transmission and thermal insulation properties. In this paper, eight aerogel glazing samples were prepared by filling aerogel particles with four different diameters into hollow glass with two different thicknesses (viz., 5 mm and 7.5 mm). The thermal and optical parameters of the aerogel glazing were experimentally measured and the day-lighting performance was calculated. A case study of the aerogel glazing installing at different positions in a large atrium building under cooling-dominant climates was carried out. The results indicate that installing aerogel glazing at the skylight with is more effective than at the outside windows. The envelope heat gain was reduced by 31% by replacing the single glazing with the HA-type aerogel glazing at skylight under the condition of indoor illumination.